Conductivity studies of grafted natural rubber and ionic liquid electrolyte systems - Rahmat, M.F.; Alias, Yatimah; Basirun, Wan Jefrey; Aldous, L.; Hardacre, C. (Faculty of Science, University of Malaya, 2009)
Ionic liquids containing the 1 -butyl- 1-methylpyrrolidinium ([C 4mPyrr]+) cation and bis(trifluoromethanesulfonyl)imide ([NTf 2]") anion have been synthesized and incorporated in 49% PMMA grafted natural rubber together with lithium salts to obtain solid polymer electrolytes (SPEs). The resultant SPEs obtained, are freestanding, flexible film and translucent and show conductivity over a wide range of 10 -3-10 -5 S cm -1. Polymer electrolytes containing 80% of (MG49:LiCF 3S0 3) and 20% of [C 4mPyrr] [NTf 2] showed the highest conductivity of 2.11 x 10 -3 S cm -1 at room temperature. The examination of the ion- polymer interactions and ionic conductivity are discussed and investigated by FT-IR and Electrochemical Impedance Spectroscopy (EIS) respectively.